Keanekaragaman dan Kelimpahan Lalat Buah (Bactrocera Sp) dan Potensi Parasitoidnya di Kebun Campuran Desa Babulu Selatan, Kabupaten Malaka - Bay, Maria Marselina; Pakaenoni, Gonsianus; Funan, Maria Adriana (Fakultas Pertanian, Sains, dan Kesehatan, Universitas Timor, 2023)
The people of Babulu Selatan Village, Malacca Regency, generally develop agriculture in the form of horticultural crops. In its development efforts, it is inseparable from the presence of Plant Disturbing Organisms (OPT) including fruit flies. The purpose of this study was to determine the diversity and abundance of fruit fly species (Bactrocera sp) associated with horticultural crops and to determine the factors that affect the diversity and abundance of fruit flies (Bactrocera sp) in mixed plantations of Babulu Selatan village, Malacca district. The research was conducted in June 2022-July 2022 in Babulu Selatan Village, Malacca Regency. This study used a qualitative approach method to describe what fruit flies damage fruits. Collection and identification of fruit flies and their parasitoids using methyl eugenol traps. Measurement of environmental factors such as temperature and humidity using thermohygrometer. The results of the study found 4 species of fruit flies namely Bactrocera dorsalis, Bactrocera carambolae, Bactrocera umbrosa and Bactrocera papayae. The results of data analysis of the highest abundance value of B. dorsalis species is 0.018 individuals m2 , the value of B. umbrosa species is 0.0132 individuals m2 , the value of B. carambolae species is 0.0128 individuals m2 , while the lowest species value is B. papayae species with a value of 0.012 individuals m2 . However, no fruit fly parasitoids were found from the study site. Temperature measurements ranged from 24ºC - 29ºC and humidity ranged from 90%-150%. B. dorsalis was found the most because it was able to live and survive at a temperature of 26ºC and 90% humidity, while B. umbrosa and B. papayae were the lowest because of their tolerance of 30ºC and 110% humidity.